Industrial training report: Mission Food Benefactor Sdn Bhd / Muhammad Iskandar Aliff Idris - Idris, Muhammad Iskandar Aliff (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report highlights the Human Resources (HR) intern's eight-week industrial training experience at Mission Foods Sdn. Bhd. The internship gave me practical experience with HR functions, such as hiring, relationship with workers, processing payroll, and administrative assistance. Among the key duties were helping to screen and shortlist candidates, setting up interview times, keeping track of staff, and helping to plan programs for training. The internship improved knowledge of employment laws and safety in the food production industry while boosting the development of practical skills including communication, time management, and problem-solving. Through cooperation and mentoring, difficulties like handling employee enquiries and understanding complicated payroll systems were minimised. In addition to improving technical HR skills, this experience highlighted the value of flexibility and lifelong learning for professionals.